The role of Web 2.0 in collaborative design: an ANT perspective - Chitanana, Lockias (Springer, 2021)
This paper analyses Web 2.0 facilitated collaborative design among undergraduate engineering students. The study used the actor–network theory as a methodological and analytical framework to study the role of Web 2.0 technology in the collaborative design process. Participants were drawn from fourth-year engineering students at a university of technology in Zimbabwe. Data were constituted by using a questionnaire, comprising closed and open-ended questions, semi-structured interview schedules, observation schedules, and non-participant observation of online activities by student designers. The findings of the study show that Web 2.0 technology stirred the collaborative design process by stimulating unpredictable actions, thus actively contributing to shaping the emerging collaborative design network. The study concludes that Web 2.0 technologies should not be viewed as simple tools for communication, as described in some literature but as non-human actors which can mediate the collaborative design process and shape the way it is constitued and carryed out in practice.